PENGENTASAN KEMISKINAN BERBASIS GENDER PADA PROGRAM KAMPUNG TEMATIK (STUDI KASUS: KAMPUNG JAJANAN TRADISIONAL, PUDAKAPAYUNG) - Wanda Triatmoko; Landung Esariti (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
Poverty is a common problem for urban development. Semarang is a city that strives to reduce the poverty rate. The thematic village program is one of the programs to reduce the poverty rate. Some thematic village are still not effective in reducing the poverty rate in Semarang because the theme does not comply with local conditions, the activities have not implemented gender mainstreaming strategy and not able to increase the income of the people. The purpose of this study is to examine about poverty alleviation model in thematic village program base on gender mainstreaming in traditional snack village, Pudakpayung Semarang. This study used quantitative methods with descriptive and scoring analytical techniques. The results showed that the thematic village program in traditional snack village has been able to reduce the poverty rate in Semarang City. That is because the program has implemented the rules in the gender mainstreaming so that it impacts on the increase in revenue, reduction of the unemployment rate, and able to meet the needs of the people's lives. The recommendation given is the granting of tax relief to poor entrepreneurs and providing access to capital and marketing.